Tobacco use in pregnant women: analysis of data from Demographic and Health Surveys from 54 low-income and middle-income countries - Dr. Rishi Caleyachetty, PhD; Christopher A Tait, MPH; Andre P Kengne, PhD; Camila Corvalan, PhD; Prof. Ricardo Uauy, PhD; Justin B Echouffo-Tcheugui, PhD (Elsevier, 2014)
Background: Worldwide, use of tobacco is viewed as an important threat to the health of pregnant women and their children. However, the extent of tobacco use in pregnant women in low-income and middle-income countries (LMICs) remains unclear. We assessed the magnitude of tobacco use in pregnant women in LMICs. Methods: We used data from Demographic and Health Surveys (DHS) done in 54 LMICs between Jan 1, 2001, and Dec 1, 2012, comprising 58 922 pregnant women (aged 15-49 years), which were grouped by WHO region. Prevalence of current tobacco use (smoked and smokeless) was estimated for every country. Pooled estimates by regions and overall were obtained from random-effects meta-analysis. Findings: Pooled prevalence of any tobacco use in pregnant women in LMICs was 2·6% (95% CI 1·8-3·6); the lowest prevalence was in the African region (2·0%, 1·2-2·9) and the highest was in the Southeast Asian region (5·1%, 1·3-10·9). The pooled prevalence of current tobacco smoking in pregnant women ranged from 0·6% (0·3-0·8) in the African region to 3·5% (1·5-12·1) in the Western Pacific region. The pooled prevalence of current smokeless tobacco use in pregnant women was lowest in the European region (0·1%, 0·0-0·3) and highest in the Southeast Asian region (2·6%, 0·0-7·6). Interpretation: Overall, tobacco use in pregnant women in LMICs was low; however high prevalence estimates were noted in some LMICs. Prevention and management of tobacco use and exposure to second-hand smoke in pregnancy is crucial to protect maternal and child health in LMICs. Funding: None.